The Vibrio cholerae VprA-VprB Two-Component System Controls Virulence through Endotoxin Modification - Carmen M. Herrera (American Society for Microbiology, 2014)
ABSTRACT The bacterial cell surface is the first structure the host immune system targets to prevent infection. Cationic antimicrobial peptides of the innate immune system bind to the membrane of Gram-negative pathogens via conserved, surface-exposed lipopolysaccharide (LPS) molecules. We recently reported that modern strains of the global intestinal pathogen Vibrio cholerae modify the anionic lipid A domain of LPS with a novel moiety, amino acids. Remarkably, glycine or diglycine addition to lipid A alters the surface charge of the bacteria to help evade the cationic antimicrobial peptide polymyxin. However, the regulatory mechanisms of lipid A modification in V. cholerae are unknown. Here, we identify a novel two-component system that regulates lipid A glycine modification by responding to important biological cues associated with pathogenesis, including bile, mildly acidic pH, and cationic antimicrobial peptides. The histidine kinase Vc1319 (VprB) and the response regulator Vc1320 (VprA) respond to these signals and are required for the expression of the almEFG operon that encodes the genes essential for glycine modification of lipid A. Importantly, both the newly identified two-component system and the lipid A modification machinery are required for colonization of the mammalian host. This study demonstrates how V. cholerae uses a previously unknown regulatory network, independent of well-studied V. cholerae virulence factors and regulators, to respond to the host environment and cause infection. IMPORTANCE Vibrio cholerae, the etiological agent of cholera disease, infects millions of people every year. V. cholerae El Tor and classical biotypes have been responsible for all cholera pandemics. The El Tor biotype responsible for the current seventh pandemic has displaced the classical biotype worldwide and is highly resistant to cationic antimicrobial peptides, like polymyxin B. This resistance arises from the attachment of one or two glycine residues to the lipid A domain of lipopolysaccharide, a major surface component of Gram-negative bacteria. Here, we identify the VprAB two-component system that regulates the charge of the bacterial surface by directly controlling the expression of genes required for glycine addition to lipid A. The VprAB-dependent lipid A modification confers polymyxin B resistance and contributes significantly to pathogenesis. This finding is relevant for understanding how Vibrio cholerae has evolved mechanisms to facilitate the evasion of the host immune system and increase bacterial fitness.